Predicting decline of kidney function in lupus nephritis using urine biomarkers. (August 2016) - Abulaban, K M; Song, H; Zhang, X; Kimmel, P L; Kusek, J W; Nelson, R G; Feldman, H I; Vasan, R S; Ying, J; Mauer, M; Nelsestuen, G L; Bennett, M; et al.
Objective: To evaluate candidate biomarkers to predict future renal function decline (RFD) in children and adults with lupus nephritis (LN). Methods: At the time of enrollment into prospective observational LN cohort studies liver-type fatty acid binding protein (LFABP), albumin, monocyte chemoattractant protein-1 (MCP-1), uromodulin, transferrin, and hepcidin were measured in urine samples of two cohorts of patients with LN, one followed at a pediatric (cohort-1; n = 28) and one at an adult institution (cohort-2; n = 69). The primary outcome was RFD, defined in cohort-1 as a decrease in estimated glomerular filtration rate (eGFR) of ≥20% and in cohort-2 as a sustained increase of ≥25% in serum creatinine concentration (SCr), both from baseline. Results: All patients ( n = 97) had normal eGFR or SCr at the time of urine collection at baseline. RFD occurred in 29% (8/28) of patients in cohort-1 during a mean follow-up of 6.1 months, and in 30% (21/69) of those in cohort-2 during a mean follow-up of 60 months. Individually, in cohort-1, levels of MCP-1, transferrin, LFABP, and albumin were higher in the RFD group than those who maintained renal function, with statistical significance for LFABP and albumin. In cohort-2 the RFD group also had higher levels of urine MCP-1 and albumin than others. The combination of LFABP, MCP-1, albumin, and transferrin had good predictive accuracy for RFD in both cohorts (area under the ROC curve = 0.77–0.82). Conclusion: The combinatorial urine biomarker LFABP, MCP-1, albumin, and transferrin shows promise as a predictor of renal functional decline in LN, and warrants further investigation.